DOI: 10.31274/etd-180810-5950
|View full text |Cite
|
Sign up to set email alerts
|

Fulfillment of the employee psychological contract in a healthcare system: Does it drive employee engagement and reduce turnover intention?

Abstract: DEDICATIONI would like to thank my personal network and my family for supporting me during my two years of intensely devoted study.To my mom, whom I can thank for always setting the bar high and inspiring me to believe that I could be a CEO or anything else my heart desired. To my husband of 25 years, Victor, and our daughters, Stephanie, Lindsay, and Emma: I know that I have been distant, stressed, and mostly unavailable while juggling the pursuit of a full-time graduate degree and a full-time administrative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 138 publications
(236 reference statements)
1
6
0
1
Order By: Relevance
“…Halbesleben and Wheeler (2008) identified engagement and embeddedness as unique constructs that predict intention to leave. Studies by Bonilla (2018), Caesens et al (2016) and Kasekende (2017) found that engaged employees are less inclined towards turnover intention. In a recent work, Abela and Debono (2019) found lack of employee engagement to be one of the factors that could trigger intention to leave.…”
Section: Review Of Literaturementioning
confidence: 96%
“…Halbesleben and Wheeler (2008) identified engagement and embeddedness as unique constructs that predict intention to leave. Studies by Bonilla (2018), Caesens et al (2016) and Kasekende (2017) found that engaged employees are less inclined towards turnover intention. In a recent work, Abela and Debono (2019) found lack of employee engagement to be one of the factors that could trigger intention to leave.…”
Section: Review Of Literaturementioning
confidence: 96%
“…H4: Supervisor support positively moderates the relationship between person-organization fit and employee engagement. Bonilla (2018) claimed that the inclination toward voluntary turnover is lower for employees who are highly engaged. In their groundbreaking investigation, Abela and Debono (2019) advocated that the absence of employee engagement is highly responsible for triggering turnover intention.…”
Section: Conceptual Framework and Hypotheses Developmentmentioning
confidence: 99%
“…The social exchange theory is applied in the organization on the basis that there are appealing company actions that are intended for the employees. The lexicon of the social exchange model encompasses compensation, worth, resource, utility, reinforcement, comparison level, cost, transaction, income, and result [19]. Bentein and Guerrero [20] also positioned social exchange theory in a way that explains the workplace from the perspective of the employees.…”
Section: Theoretical Reviewmentioning
confidence: 99%